Trigeminocardiac reflex and haemodynamic changes during Le Fort I osteotomy. Issue 5 (May 2016) - Kiani, M.T.; Tajik, G.; Ajami, M.; Fazli, H.; Kharazifard, M.J.; Mesgarzadeh, A.
Abstract: The Le Fort I osteotomy is performed under general anaesthesia and specific haemodynamic conditions, i.e. hypotensive general anaesthesia. This study assessed the incidence of the trigeminocardiac reflex (TCR) during the different stages of the Le Fort I osteotomy. Forty-seven patients requiring a Le Fort I osteotomy were included. General anaesthesia was induced. In terms of haemodynamic changes, each patient's oxygen saturation (SpO2 ), mean arterial pressure (MAP), heart rate (HR), and electrocardiogram (ECG) were monitored by SADAAT Monitoring System and recorded during the different stages of osteotomy: before the induction of anaesthesia, before osteotomy cuts, after finishing the right pterygoid plate osteotomy, after finishing the left pterygoid plate osteotomy, and after performing down-fracture of the maxilla. No significant alteration in haemodynamic values was seen at the different stages of Le Fort I osteotomy. One patient showed arrhythmia with non-sinus junction rhythm after sinus bradycardia and two premature atrial contractions in the down-fracture stage, which led to the abrupt cessation of the procedure by the surgeon. This study showed no significant alterations in haemodynamic values during the different stages of Le Fort I osteotomy. Halting the procedure momentarily was sufficient to allow spontaneous normalization of the HR, blood pressure, and dysrhythmia.